Species and functional diversity of native and human-dominated plant communities - Mayfield, M; Boni, M; Daily, G; Ackerly, D (2005)
Despite growing attention to how human activities alter plant communities, little is known about the ecosystem consequences of these changes. We explore the relationship between species and functional diversity of herbaceous and shrubby plant communities in forested and deforested habitats in three Neotropical landscapes. We focus on six traits: pollination mechanism, dispersal mechanism, growth form, fruit type, fruit size, and seed size. We ask: (1) What is the relationship between species richness and functional diversity (trait state richness)? (2) Do species/functional diversity relationships differ between forested and deforested habitats? and (3) Are observed species/functional diversity patterns more consistent with ecological filtering or differentiation-based assembly processes? We show that species richness is often a weak surrogate for functional diversity, depending on the trait. Species/functional diversity relationships differ significantly between forested and deforested habitats, but the nature of differences is trait dependent. Dispersal mechanism and fruit type number increased more rapidly in deforested than forested habitats, but the opposite was true for most other traits. Using a null model, we found evidence of ecological filtering for most traits in both habitats. Results demonstrate that deforested habitats do not necessarily contain lower functional diversity than forest but that the ecological assembly processes influencing community function in deforested communities differ dramatically from forest. © 2005 by the Ecological Society of America.